The communication pattern in prosumption practices through free e-books at membacacepat.com - Wibowo, Tangguh Okta (Faculty of Communications Science, Dr. Soetomo University, 2022)
This study explored the occurrence of a free e-book titled Speed Reading for Beginners that can only be obtained by signing up for an email newsletter at MembacaCepat.com. Through Web 2.0, the Internet facilitated the emergence of a new culture centred on shifting consumer relationships in which individuals both consumed and produced the products they consumed. The purpose of this study is to carry out further research into the communication pattern regarding how the practices of production and consumption, also known as prosumption, occurred at the same agency via the web manager or web owner and e-book downloaders. This study employs virtual ethnography by interviewing informants and observing artefacts as data via the Internet. This study aims to utilise the circuit of culture as an analytic framework, similar to the consumption circuit outlined in continuing consumption practices. The findings indicate that the pattern of production and consumption can be mapped as a collaborative effort between website owners and visitors, with the Speed Reading for Beginners e-book catalysing increased visitor participation.